Content analysis in light of Bloom's classification of soccer questions from (2014) to (2019) methodology For third stage students (Journal of the College of Basic Education, 2022)
The importance of examinations is due to the importance of education and the goal of achieving it, as its importance is demonstrated through its inculcation of social, cultural and social values, love for the homeland and the identification of the rights and duties of each individual and thus the formation of good citizensQuestions took their distinctive place in the educational process, as they provide teachers with the basic functions for their success in their lessons. Perhaps the most popular classifications spread in the field of education is Bloom's Classification, where he classified the six levels (knowledge, understanding, application, analysis, synthesis, evaluation), where he arranged these levels in a hierarchical manner, beginning with the level of (knowledge) that represents the base of the pyramid and ending with the level of (evaluation), which represents the top Pyramid Bloom sets six levels and the questions require the person responding at any level to use a special type of thinking process. The teacher and teacher should be able to formulate questions including for each of Bloom’s six levels so that the student can participate in the various cognitive processes. Hence the importance of analysis. Examination questions to their six levels, as well as the fit of ideas with the goals set.The questions of the monthly exams on the theoretical side used in the subject of football are often unclear and incomprehensible according to the Bloom level classification for organizing the stages of building the question paragraphs, as these questions are often incapable of stimulating students' thinking, as well as the fact that most of the questions are overshadowed by the nature of routine and the inability to develop mental processes I have a student.As for the research problem, most of the questions of the monthly exams on the theoretical side followed in the subject of football are often unclear and incomprehensible according to the Bloom level classification to organize the stages of building the paragraphs of the questions, as these questions are often unable to stimulate the thinking of students, as well as the fact that most of the questions are overshadowed by the character Routine and inability to develop the student's mental processes.In light of this, the aim of the research was the aim of the current research to analyze the content in light of Bloom's classification of soccer questions from 2014 to 2019 methodology for students of the Department of Physical Education and Sports Sciences / Third Stage in the College of Basic Education / Al-Mustansiriya UniversityThe assumption of the research was that there are basic principles for content analysis in light of Bloom's classification of soccer questions from 2014 to 2019 methodology for third-year students in the Department of Physical Education and Sports Sciences / College of Basic Education / Al-Mustansiriya University.The second chapter included the procedures, the research community, the sample, and the statistical methodsWhile the third chapter includes the presentation and analysis of the resultsThe fourth chapter included the conclusion that the examination questions were limited to (knowledge, understanding, and application) and did not pay attention to (analysis, synthesis, evaluation) according to Bloom's classification of the field of knowledge.The recommendations were to emphasize the consideration of placing the balanced questions of Bloom levels in the soccer